Information and its impact on the sectoral structural change of the economy - Baranov, Alexander M.; Lemeschenko, Petr S. (Journal of the Belarusian State University. Economics, 2023)
The article systematises methodological approaches to the research of the sectoral structure of the economy, taking into account modern information innovations. The radical transformations that were implemented into traditional sectors by the information and intellectual component are interiorised. The model of interrelations between the sectors of the traditional and new economy in the structure of the national economic system is developed. Modern trends in the development of the information and agricultural sector in developed countries and Belarus are considered. Institutional and legal regulation of the digital transformation of industry in the USA and EU countries are systematised. Comparative analysis of foreign experience in correlation with Russia and Belarus are conducted. On the basis of current foreign trends in terciarisation, the development of science and education, the new sector of the economy – the meta-sector of information and anthropogenic services is proposed. The role of the state in the formation of the institutional contour of the information economy is considered.